A Brand Image of E-Commerce's Buying Interest - Amelia, Windi Amanda (Journal of Economicate Studies, 2020)
This article discusses the brand image of ecommerce buying interest. The methods used in this study are the literary methods that are sourced in books, research reports, journals and websites. This article finds that brand imagery serves as a strategy to safeguard and increase consumer interest, a positive brand image can make it easier for consumers to realize their interest in e-commerce.